Drug Flow Through Clinical Infusion Systems: How Modeling of the Common-volume Helps Explain Clinical Events - Lovich Mark A.; Peterfreund Robert A. (De Gruyter, 2017)
This review aims to describe analytic models of drug infusion that demonstrate the impact of the infusion system common-volume on drug delivery. The common-volume of a drug infusion system is defined as the volume residing between the point where drug and inert carrier streams meet and the patient's blood. We describe 3 sets of models. The first is quantitative modeling which includes algebraic mathematical constructs and forward-difference computational simulation. The second set of models is with in vitro benchtop simulation of clinical infusion system architecture. This modeling employs devices including pumps, manifolds, tubing and catheters used in patient care. The final set of models confirms in vitro findings with pharmacodynamic endpoints in living large mammals. Such modeling reveals subtle but important issues inherent in drug infusion therapy that can potentially lead to patient instability and morbidity. The common-volume is an often overlooked reservoir of drugs, especially when infusions flows are slowed or stopped. Even with medications and carriers flowing, some mass of drug always resides within this common-volume. This reservoir of drug can be inadvertently delivered into patients. When infusions are initiated, or when dose rate or carrier flow is altered, there can be a significant lag between intended and actual drug delivery. In the case of vasoactive and inotropic drug infusions, these unappreciated time delays between intended and actual drug delivery can lead to iatrogenic hemodynamic instability. When a drug infusion is discontinued, drug delivery continues until the common-volume is fully cleared of residual drug by the carrier. The findings from all 3 sets of models described in this review indicate that minimizing the common-volume of drug infusion systems may enhance patient safety. The presented models may also be configured into teaching tools and possibly point to technological solutions that might mitigate sources of iatrogenic patient lability.